Determination of an instrumental method for measuring hardness in whole cooked beans (Phaseolus vulgaris L.) - Artavia-Vindas, Fulvio (2024)
Introduction. Hardness measurement of cooked beans in Costa Rica is conducted using a sensory method and without a standardized instrumental method. Objective. To determine a potential instrumental method for the measuring hardness in whole cooked beans, based on a hardness analysis of two brands of canned beans marketed in Costa Rica. Materials and methods. The study was conducted at the Chemistry Laboratory of Food Technology Department at the Universidad de Costa Rica, San José, Costa Rica, from November 2019 to April 2020. Measuring of hardness were performed by placing five beans in an adjustable cell texture analyzer with a cylindrical probe (50 mm) at a compression speed of 1 mm/s, until reaching 75 % bean compression. The results of these measurements were analyzed using a 2x2 factorial treatment design, where the experimental factors were brand and container size. The levels in each factor were considered as brand: A and B, and container size: 420 g and 823 g. The required number of repetitions was then estimated to ensure a test power of 90 %. Results. Significant differences were found in the brand factor, but not in the container size factor. Power analysis results indicated that, with a 90 % power, 16 repetitions of the texture analysis are necessary. Conclusion. The specific processing of each company influences the final texture of the cooked bean. The developed methodology enables instrumental analysis of bean hardness with a 90 % test power and a number of 16 replicates.